Sustainable livelihood alternatives among Nile perch (Lates niloticus) fishers in Lake Victoria Tanzania: Analytical hierarchy process (AHP) approach - Eliaza Mkuna; Lloyd Baiyegunhi; Wiktor Adamus (Journal of Economic Structures, 2020)
Sustainable livelihood has been a focal point in many development initiatives by private and public sectors in most African countries. However artisanal fishers in the main lakes of Africa are faced with several alternative decisions to improve their liveli-hood sustainably. Several studies which have been conducted in Africa offered various options using different models such as sustainable livelihood approach/framework (SLA). This study provides different decision-making alternatives using multi-criteria decision model known as analytical hierarchy process (AHP) to assess the most economical and sustainable livelihood options for Nile perch fishers in Lake Victoria Tanzania. Using structured questionnaires and key informant interviews, different strategic criteria such as environment, economic, social and technology were analyzed and the study found that, important factor in the strategic criteria is environment. Moreover, different livelihood alternatives which include livelihood diversification, fish-eries co-management and promotion of aquaculture were analyzed. The study found that livelihood diversification which implies diversifying income-generating activities was identified as the best alternative model for sustainable livelihood development. The study recommends proper income diversification interventions and environment management for the sustainability of Nile perch fishers' livelihood and fishery resources in Lake Victoria.
Keywords: 330; Analytical hierarchy process (AHP); Nile perch fishers; Sustainable livelihood